Prevalence of Vitamin D level deficiency among patients with non-specific musculoskeletal pain at a tertiary care hospital in Khyber Pakhtunkhwa (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To objective of the study is to find out the prevalence of vitamin D deficiency in patients with non-specific musculoskeletal pain presenting to outpatients department at a tertiary care hospital of Khyber Pakhtunkhwa.Methods: The design of our study was cross section and was conducted on 253 patients with age above 15 years presenting to Orthopedic Out Patients Department (OPD) of a tertiary care hospital from from 21st June 2018 to 20th June 2019.These patients presented with non-specific musculoskeletal pain like generalized body aches, bone pain, weakness and fatigue with no other complaints such as fever, visceral pain and any other trauma history. Their routine test like complete blood count(CBC), Renal Function Tests(RFT),Erythrocyte Sedimentation Rate (ESR) and random blood sugar (RBS) were normal. They were screened for Vitamin D level.Results: out of 253 patients 37.94 %( n= 96) were male and 62.05% (n= 157) were female .Vitamin D deficiency was below normal in 75.49% (n= 191) patients comprising of 58.1% (n= 111) patients had deficiency and 41.8% (n= 80) had insufficiency while 24.5% ( n= 62) showed sufficient level. In comparison to other age groups Vitamin D level was deficient and insufficient in 15 to 35 age group.Conclusion: A high prevalence of vitamin D deficiency is present in our population. The Orthopaedic surgeon must keep his suspicion high for of vitamin D deficiency in patients of non specific musculoskeletal pain.